2011
DOI: 10.1111/j.1477-2574.2011.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of contemporary management of gangrenous and non-gangrenous acute cholecystitis

Abstract: Gangrenous cholecystitis has certain clinical features and associated laboratory findings that may help to differentiate it from NGAC. It is not associated with an overall increase in complications when treated in a specialized unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 12 publications
7
61
4
3
Order By: Relevance
“…C-reactive protein level was also found to be elevated in AC, especially to very high values when gangrenous cholecystitis is present and Crp level is alsocorrelated with conversion to open cholecystectomy (19)(20)(21). In our study, the mean CRP level was 79.94±93.06 mg/L in the AC group and was statistically significant as compared to the CC group (p=0.030).…”
Section: Discussionsupporting
confidence: 55%
“…C-reactive protein level was also found to be elevated in AC, especially to very high values when gangrenous cholecystitis is present and Crp level is alsocorrelated with conversion to open cholecystectomy (19)(20)(21). In our study, the mean CRP level was 79.94±93.06 mg/L in the AC group and was statistically significant as compared to the CC group (p=0.030).…”
Section: Discussionsupporting
confidence: 55%
“…1,13 Other studies have observed a similar population of older male patients being more affected by acute gangrenous cholecystitis, often with an elevation in preoperative bilirubin. 14,15 Problematically, none of the radiological findings in this study was able to predict the possibility of necrosis, giving the surgeon no warning other than clinical suspicion for this intraoperative diagnosis.…”
Section: Commentsmentioning
confidence: 73%
“…13 As one of the severe complications of acute cholecystitis, GC develops in 2% to 20% of the cases with acute cholecystitis. 5,6,14 Epithelial injury by increasing gallbladder wall tension owing to vascular insufficiency arising secondary to persistent obstruction of the cystic duct gives way to the development of GC, which follows a quite rapid course. 5 The phospholipases released from cell membranes of damaged epithelium initiate heavy inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%